Thermodynamic models for determination of the solubility of omeprazole in pure and mixture organic solvents from T = (278.15 to 333.15) K. (March 2016) - Hu, Yonghong; Wu, Gang; Gu, Pengfei; Yang, Wenge; Wang, Chunxiao; Ding, Zhiwen; Cao, Yang
Highlights: The solubility increased with increasing temperature. The data were fitted using the modified Apelblat equation and other models. The Gibbs energy, enthalpy and entropy were calculated by the van't Hoff analysis. Abstract: Data on corresponding (solid + liquid) equilibrium of omeprazole in different solvents are essential for a preliminary study of industrial applications. In this paper, the (solid + liquid) equilibrium of omeprazole in water, methanol, ethanol, 1-butanol, acetonitrile, acetone, ethyl acetate, tetrahydrofuran pure solvents and (tetrahydrofuran + ethyl acetate) mixture solvents were explored within the temperatures from 278.15 K to 333.15 K under atmosphere pressure. For the temperature range investigated, the solubility of omeprazole in the solvents increased with increasing temperature. From (278.15 to 333.15) K, the solubility of omeprazole in tetrahydrofuran is superior to other selected pure solvents. The modified Apelblat model, the Buchowski–Ksiazaczak λh model, and the ideal model were adopted to describe and predict the change tendency of solubility. Computational results showed that the modified Apelblat model has advantages than the other two models. Numerical values of the solubility were fitted using a modified Apelblat equation, a variant of the combined nearly ideal binary solvent/Redich–Kister (CNIBS/R–K) model and Jouyban–Acree model in (tetrahydrofuran + ethyl acetate) binary solvent mixture. Computational results showed that the CNIBS/R–K model is superior to the other equations. In addition, the calculated thermodynamic parameters indicate that in each solvent studied the dissolution of omeprazole is endothermic, non-spontaneous and is an entropy-driven process.